RANCANG BANGUN DC TO DC CONVERTER UNTUK SISTEM MONITORING SALINITAS AIR LAUT DENGAN PHOTOVOLTAIC SEBAGAI SUMBER ENERGI - Samad, Mohammad Syafar; Adam, Ahmad Antares; Arifin, Yusnaini; Mahmudi, Irwan; Sholihah, Ratih Mar'atus (Foristek, 2024)
Renewable energy is an energy source that can be utilized continuously and is available by nature. One example of using renewable energy is photovoltaic. Photovoltaic is a tool used to absorb solar energy and convert it into electrical energy using the photovoltaic effect method. This research aims to monitor the salinity (salt content) of sea water by utilizing solar energy using the Buck Converter type DC to DC Converter method to regulate and reduce the higher voltage to a lower voltage to be loaded on the microcontroller as the reading output. This research was designed using a 20 WP photovoltaic with a maximum voltage of 20 volts which functions as a power supplier or energy source whose voltage is then reduced by a buck converter circuit to a smaller voltage of 5 volts to be charged to the Arduino Uno in processing salinity measurement data using a TDS sensor. as a measuring tool. The test results of the equipment show that the DC to DC Converter circuit is successful in reducing the photovoltaic voltage so that it can operate the microcontroller.